Value-Based Communication Strategies and Institutional Image Formation in Islamic Philanthropy - Prathama, Lheo Sandri; Mulyadi, Mulyadi; Nasution, Nadya Amalia (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study examines how Islamic philanthropic institutions build their organizational image through value-based communication strategies, using The National Board of Zakat Lampung Province as a case study. Focusing on the integration of digital communication, Islamic values, and transparency in zakat management, the research identifies three core strategic mechanisms: (1) leveraging digital platforms to disseminate program information and financial reports, (2) reinforcing messages grounded in Islamic principles, and (3) applying transparency practices to enhance public trust. These mechanisms collectively shape the institution’s image as trustworthy, professional, and adaptive to technological developments. The findings contribute to the theory of strategic communication in Islamic philanthropy by highlighting a model that integrates religious values with digital transparency and offering practical guidance for philanthropic organizations seeking to strengthen institutional legitimacy and public engagement.